2019
DOI: 10.1016/j.jpor.2018.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Effect of laser groove treatment on shear bond strength of resin-based luting agent to polyetheretherketone (PEEK)

Abstract: The shear bond strength between PEEK and resin-based luting agent was substantially improved by laser groove treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
40
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(49 citation statements)
references
References 28 publications
2
40
1
Order By: Relevance
“…11 Sturz et al 42 used confocal laser scanning measurements to determine the surface roughness of materials. In the present study, as in other previous studies, 11,25,36,37,[39][40][41] a noncontact profilometer was used to measure the surface roughness.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…11 Sturz et al 42 used confocal laser scanning measurements to determine the surface roughness of materials. In the present study, as in other previous studies, 11,25,36,37,[39][40][41] a noncontact profilometer was used to measure the surface roughness.…”
Section: Discussionmentioning
confidence: 96%
“…In previous studies, 11,[37][38][39][40] PEEK specimens were sectioned from PEEK cylinders or disks with a low-speed diamond saw, and Çulhao glu et al 41 and Caglar et al 36 milled specimens from PEEK blocks. Similarly, HPP specimens in the present study were milled from blocks.…”
Section: Discussionmentioning
confidence: 99%
“…Researchers have recently focused on laser application to enhance the bonding of different dental materials such as ceramics and resin-based materials. 15,17,28,31,[40][41][42][43] The Er:YAG laser is the most commonly used laser type for the surface treatment of dental materials. 29,31 Different energy levels of the Er:YAG laser have been used by investigators.…”
Section: Discussionmentioning
confidence: 99%
“…[25][26][27] On the other hand, the majority of studies on the surface treatment of PEEK with lasers have focused on the bond strength of PEEK to resin cement and have reported controversial results. 15,17,28 A search of the literature by the authors revealed one previous study on the effect of Er:YAG laser treatment on bond strength of composite resin veneers to PEEK. They observed that a combination of airborne-particle abrasion or silica coating with Er:YAG laser irradiation provided a durable bond while the Er:YAG laser beam alone did not enhance the bond strength.…”
Section: Introductionmentioning
confidence: 99%
“…In the last decade, with the advancement of laser techniques, the use of lasers as an alternative pretreatment method for dental procedures has become prevalent, such as by applying laser treatment to dental materials to improve the bonding properties between materials and resin-based luting agents [24] or materials and porcelain [25]. This resulted in the attempted use of lasers as a surface treatment method for zirconia ceramics, in order to enhance the bonding strength and durability of a number of dental materials by altering the surface microstructures [26][27][28].…”
Section: Introductionmentioning
confidence: 99%